How does Energy Consumption Affect Sectorial Value Addition? An Empirical Evidence from SAARC Economies - Naqvi, Syed Kafait Hussain; Zahra, Hafiza Sadaf; Khan, Gohar (Pakistan Journal of Humanities and Social Sciences, 2023)
Understanding the significant role of energy in key sectors is a substantial element for energy planning and policy of an economy. In the context of global energy demand and scarcity issues, the current study is an attempt to explore the role of Energy Demand at the sectorial level of the SAARC economies by using value addition of key sectors as a starting point. To address the objectives of the study, and to explore the dynamic relationship among the variables, dynamic simultaneous panel data models are employed. In this context, the study employed Generalized Method of Moment (GMM) as an estimation technique. The findings demonstrate positive and significant impact of Energy Demand on Agriculture and Industrial Value added growth while a negative impact on Services Value Added growth has been found. Similarly, the conventional growth factors such has Human capital and Physical capital along with Population Growth contributed positively and significantly to the sectorial value addition growth. On the basis of these empirical findings the study suggests that Energy allocation towards Agriculture and Industrial sector must be focused to achieve potential economic growth of the SAARC economies.